All Equal: Article 198 of the Objective of Civil Procedure Code - Gomes, Luciane Mara Correa (2016)
The implementation of the electronic process in Brazil was made to be a way to minimize the slowness in dealing with cases. Created the first barrier of inequality, because there was not the adequacy of the system to people with special needs. The Civil Procedure Code calls for equal treatment by imposing the Judiciary duty purpose of access, spreading the installation charge of treatment rooms with technical support and personnel to jurisdictional, disabled and elderly. In the absence of physical space, allows the law to practice through physical, creating imbalance in parity procedural weapons.